2018
DOI: 10.1016/j.clgc.2018.07.008
|View full text |Cite|
|
Sign up to set email alerts
|

Survival Outcomes, Prostate-specific Antigen Response, and Tolerance in First and Later Lines of Enzalutamide Treatment for Metastatic Castration-resistant Prostate Cancer: A Real-World Experience in Hong Kong

Abstract: In the real-life setting, there was a higher incidence of enzalutamide-related fatigue than reported in the trials. Earlier lines of enzalutamide treatment were associated with longer PFS and OS, more frequent PSA response, and less fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…In post-chemotherapy mCPRC patients, the median OS with enzalutamide treatment was 10.3 months in a study performed in Japan and 15.8 months in a study done in Hong Kong 20,21 . A Korean study reported a median OS of 17.7 months with enzalutamide treatment for chemotherapy-naive mCRPC patients 22 .…”
Section: Discussionmentioning
confidence: 97%
“…In post-chemotherapy mCPRC patients, the median OS with enzalutamide treatment was 10.3 months in a study performed in Japan and 15.8 months in a study done in Hong Kong 20,21 . A Korean study reported a median OS of 17.7 months with enzalutamide treatment for chemotherapy-naive mCRPC patients 22 .…”
Section: Discussionmentioning
confidence: 97%
“…We published two reports of real-life experience using abiraterone and enzalutamide in the Hong Kong Chinese population. Apart from slightly higher rates of hypertension and peripheral oedema with abiraterone [ 32 ], and hypertension and fatigue with enzalutamide [ 33 ], our mCRPC patients experienced similar rates of severe adverse events as those in pivotal studies [ 34 , 35 , 36 , 37 ]. The differences might, to some extent, be attributable to our inclusion of patients with higher baseline prostate-specific antigen (PSA) levels and Gleason scores, as well as reporting differences (fatigue was physician-reported in real-life, but self-reported in trials).…”
Section: Drug Tolerability In Asian Patientsmentioning
confidence: 87%
“…In the AFFIRM trial, pretreatment ALP and LDH levels were correlated with PSA value [27]. Moreover, ALP level prior to enzalutamide treatment has been proven to be a strong predictor of progression-free survival in a real-world cohort [28]. Furthermore, it has been observed in several mCRPC series that the higher the LDH value before treatment with enzalutamide or abiraterone, the poorer the progression-free survival [29][30][31].…”
Section: Discussionmentioning
confidence: 99%